2016
DOI: 10.1503/jpn.150207
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine cue–induced dopamine release in the human prefrontal cortex

Abstract: IntroductionThe prefrontal cortex (PFC) integrates and interprets sensory information, processing value, directing attention, and planning actions based on experience.1,2 In cocaine-dependent individuals, these regions and processes are engaged by drug-related cues, increasing the likelihood of craving and drug pursuit.3-5 For each of these effects, dopamine (DA) is a plausible contributing transmitter. Mesocortical DA transmission plays a critical role in cognitive and executive functions, 6 and, in laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 70 publications
(104 reference statements)
3
56
0
Order By: Relevance
“…Decreased D 2 autoreceptor expression may be associated with greater amphetamine-induced DA release in the LS ( vs . other striatal regions) [28],[54], though the effect of fewer DATs is less clear [38],[55]. The LS also sends non-reciprocal GABAergic projections to the ASTS, as such, ASTS activity is regulated by LS GABAergic input (similarly, the ASTS appears to regulate the SMS via GABA projections) [38],[55].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased D 2 autoreceptor expression may be associated with greater amphetamine-induced DA release in the LS ( vs . other striatal regions) [28],[54], though the effect of fewer DATs is less clear [38],[55]. The LS also sends non-reciprocal GABAergic projections to the ASTS, as such, ASTS activity is regulated by LS GABAergic input (similarly, the ASTS appears to regulate the SMS via GABA projections) [38],[55].…”
Section: Discussionmentioning
confidence: 99%
“…101105 Imaging studies have also revealed that cues associated with cocaine craving increase dopamine release in the striatum, amygdala, and prefrontal cortex (anterior cingulate and medial orbitofrontal cortex) and opioid peptides in the anterior cingulate and frontal cortex. 9,31,106,107 Indeed, imaging studies have revealed baseline decreases in orbitofrontal (medial and lateral) and anterior cingulate (ventral and dorsal) function and dopamine function during dependence, but reactivation of dopamine and reward system function during acute craving episodes. 108 …”
Section: Neurobiological Mechanisms Of the Preoccupation/anticipationmentioning
confidence: 99%
“…This experiment was designed to measure the effects of presentation of a Pavlovian cue previously associated with IV injections of cocaine on the activity of two major neuromodulatory inputs to the prefrontal cortex, dopamine (DA) and ACh. We hypothesized that STs would express their preference for cue‐directed behaviour and that increases in cortical extracellular DA levels would be associated with their bias for processing of the motivational attributes of the cocaine cue, as has been described in cocaine addicts (Milella et al ., ). Furthermore, in STs, such cue‐evoked increases in prefrontal DA levels may stabilize such cue‐directed behaviour, even under extinction conditions (Ellwood et al ., ).…”
Section: Introductionmentioning
confidence: 97%